Analyzing User Experience of Website for the Learning of Programming Language - Derisma, Derisma (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2020)
User experience is a term for the experience of users in having an easiness and efficiency in the interaction between humans and computers. CodeSaya is an easy, fun, and free place to learn about coding. There are some Programming Languages which can be learned. This research aimed to analyze the effectiveness of the codesaya.com website to learn the basics of programming by using a measurement method of the User Experience Questionnaire (UEQ). There are six examined scales, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The testing results showed that those six scales positively affected the students' attentions to use the programming framework with 1.722 of attractiveness score, 1.456 of perspicuity score, 1.718 of efficiency score, 1.46 of dependability score, and 1.44 of stimulation score, these scores showed that the five scales were at a high level, while novelty was at a moderate level with 1.147 of the score. According to the whole data processing and analysis were done in this study, it can be concluded that CodeSaya Website can improve the learning effectiveness of Programming Languages.